(untitled) (Papeles, 2024)
Introduction: The reading of multimodal texts, specifically comics, requires that teachers in training have knowledge of the disciplinary-didactic domains for their teaching. However, in the current educational context, research has shown that they do not have the essential knowledge to use comics in the classroom and show little training in this regard. In view of this situation, it is necessary to create specific courses on the didactics of reading comics so that teachers in training obtain this learning and can perform optimally in their teaching practice. This article presents the design and implementation of a training program for the teaching of comic book reading, together with the analysis of the participants’ evaluations of the disciplinary-didactic domains and the training methodology used. Methodology: A qualitative perspective was used, specifically a collective case study in which 12 students of Pedagogy in Spanish from a private university in Santiago de Chile participated. The data were collected through a focus group and a thematic analysis was applied with Atlas.ti 23 software. Results: It is observed that the evaluations made by the participants focus on positive and negative statements about the disciplinary-didactic domains for the teaching of comic book reading and the methodology used. Conclusion: We present the contributions and pedagogical lessons learned that should be considered for the design of Initial Teacher Training programs for the teaching of comic book reading in the secondary education classroom.